Pengembangan Web Support Untuk Siswa Sekolah Menengah Atas Jurusan IPA Pokok Bahasan Trigonometri - Kurniawan, Haris; Zulkardi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2017)
The purpose of this study were 1) to produce Website Support Programs for high school students on the topic of Trigonometry IPA valid and practical. 2) to investigate the potential effects Support Website developed against the interests of high school students on the subject of the Department of Science Trig in SMAN 2 Sekayu, SMAN 4 Lahat. The study was conducted through two steps, namely 1) premilinery phase covers all the initial preparations. 2) Prototyping includes pendesaianan process, development and formative evaluation. The method of collecting the data in the form of a walk trough, Questionnaire. The results of this development is in the form of a support website for high school students majoring in science subjects trigonometry, with www.trigonometrisma.com address. This website has been categorized valid views of the validation process conducted by linguist, an expert in web design, mathematical practitioners, and is said to be practical after testing to field test showed positive results based on the comments and questionnaires from students. Based on field tests note that this website has the potential effects on student interest of the results of questionnaire analysis, especially in terms of readiness there are 70.4% who said they want to linger - long on this website or at home and on the analysis of the test menu.